Long term follow-up of cervical intervertebral disc herniation inpatients treated with integrated complementary and alternative medicine: a prospective case series observational study. Issue 1 (December 2015) - Baek, Sang; Oh, Jae; Shin, Joon-Shik; Lee, Jinho; Lee, Yoon; Kim, Me-riong; Ahn, Yong-jun; Choi, Areum; Park, Ki; Shin, Byung-Cheul; Lee, Myeong; Ha, In-Hyuk
Abstract Background Symptomatic cervical intervertebral disc herniation (IDH) presenting as neck pain accompanied by arm pain is a common affliction whose prevalence continues to rise, and is a frequent reason for integrative inpatient care using complementary and alternative medicine (CAM) in Korea. However, studies on its long term effects are scarce. Methods A total 165 patients with cervical IDH admitted between January 2011 and September 2014 to a hospital that provides conventional and Korean medicine integrative treatment with CAM as the main modality were observed in a prospective observational study. Patients underwent CAM treatment administered by Korean medicine doctors (KMDs) in accordance with a predetermined protocol for the length of hospital stay, and additional conventional treatment by medical doctors (MDs) as referred by KMDs. Short term outcomes were assessed at discharge and long term follow-ups were conducted through phone interviews after discharge. Numeric rating scale (NRS) of neck and radiating arm pain, neck disability index (NDI), 5-point patient global impression of change (PGIC), and factors influencing long term satisfaction rates in PGIC were assessed. Results Of 165 patients who received inpatient treatment 20.8 ± 11.2 days, 117 completed the long term follow-up up at 625.36 ± 196.7 days post-admission. Difference in NRS between admission and discharge in the long term follow-up group (n  = 117) was 2.71 (95 % CI, 2.33, 3.09) for neck pain, 2.33 (95 % CI, 1.9, 2.77) for arm pain, and that of NDI 14.6 (95 % CI, 11.89, 17.32), and corresponding scores in the non-long term follow-up group (n  = 48) were 2.83 (95 % CI, 2.22, 3.45) for neck pain, 2.48 (95 % CI, 1.84, 3.12) for arm pain, and that of NDI was 14.86 (95 % CI, 10.41, 19.3). Difference in long term NRS of neck pain and arm pain from baseline was 3.15 (95 % CI, 2.67, 3.64), and 2.64 (95 % CI, 1.99, 3.29), respectively. PGIC was reported to be "satisfactory" or higher in 79.5 % of patients at long term follow-up. Conclusions Though the observational nature of this study limits us from drawing a more decisive conclusion, these results suggest that integrative treatment focused on CAM in cervical IDH inpatients may achieve favorable results in pain and functional improvement. Trial registration ClinicalTrials.gov Identifier:NCT02257723 . Registered October 2, 2014.